Improving students' essay writing skills by implementing peer feedback - Fatimah, Nur; Madya, Suwarsih (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
The aim of this research is improving the students' writing skill by implementing peer feedback. This study was a three cycle classroom action research at the English Education Department of Ahmad Dahlan University (UAD), Yogyakarta. It focused on the four aspects:designing and teaching the writing class implementing peer feedback, providing writing materials, varying tasks and enhancing students' participation and interaction with peers in the learning process. The subjects consisted of 22 semester 4 students of Essay Writing-Class E. The quantitative data were collected through students' essay scores, whereas the qualitative data were through fieldnotes, interview and portfolio. The research results in these findings. First, the students' participation in the learning process is enhanced through their pair work, group work and whole class activity. By working collaboratively, the students take advantages of giving feedback improving their essay on these aspects:organization, content, grammar, spelling, punctuation, and mechanics, style and quality of expression. Second, the students' essay writing improves after peer feedback.Their essay mean scores increase from 63.09; 67.23 to 70.09.